Pengaruh Organisasi bagi Mahasiswa dalam Pendidikan Karakter di Universitas Negeri Padang - Tesa, Aulia Rahma; Slipilia, Intan (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
Students have a strategic role as agents of social change that require strong character building. Padang State University (UNP), as an institution of higher education, provides various platforms for self-development through student organizations such as BEM, HMJ, UKM, and extra-campus organizations. This research aims to analyze the influence of student involvement in organizations on the formation of character education, through a literature study approach. The results of the study show that student organizations play a significant role in developing character values such as leadership, responsibility, cooperation, discipline, and social care. Organizations are also effective contextual learning media in developing soft skills and emotional maturity of students. However, the challenge of balancing organizational and academic activities needs to be a common concern. Therefore, the support of educational institutions in the form of guidance, training, and recognition of organizational activities is an important factor in maximizing the role of organizations as a means of student character education.